Mechanistic Insights on Reduction of Carboxamides by Diisobutylaluminum Hydride and Sodium Hydride−Iodide Composite. Issue 9 (21st August 2019) - Ong, Derek Yiren; Watanabe, Kohei; Takita, Ryo; Chiba, Shunsuke
Abstract: The reaction mechanisms on reduction of tertiary carboxamides by diisobutylaluminum hydride (DIBAL) and sodium hydride (NaH)‐sodium iodide (NaI) composite were elucidated by the computational and experimental approaches. Reduction of N, N ‐dimethyl carboxamides with DIBAL provides the corresponding amines, whereas that with the NaH−NaI composite exclusively forms aldehyde even at high reaction temperature. DFT calculations revealed that dimeric structural nature of DIBAL and Lewis acidity on its Al center play crucial role to decompose the tetrahedral anionic carbinol amine intermediate through C−O bond cleavage. On the other hand, in the reduction with the NaH−NaI composite, the resulting tetrahedral anionic carbinol amine intermediate could be kept stable, thus providing aldehydes as a sole product by the aqueous workup Abstract :